Экспериментальная оценка основных электрических характеристик сильноточного плазменного канала подводного искрового разряда в цепи высоковольтного генератора импульсной компоненты тока искусственной молнии - Баранов, М.И. (Електротехніка і електромеханіка, 2011)
Numerical values of ohmic resistance, specific conductivity and intensity of the longitudinal electric field are experimentally obtained for the heavy-current plasma channel of an underwater spark discharge in the circuit of a powerful generator with a capacitive storage applied for artificial lightning current pulse A-component formation with the magnitude under 200 kA.